Development, Characterization, and Immunomodulatory Evaluation of Carvacrol-loaded Nanoemulsion - Amanda Gabrielle Barros Dantas (Molecules, 2021)
Carvacrol (CV) is an essential oil with numerous therapeutic properties, including immunomodulatory activity. However, this effect has not been studied in nanoemulsion systems. The objective of this study was to develop an innovative carvacrol-loaded nanoemulsion (CVNE) for immunomodulatory action. The developed CVNE comprised of 5% w/w oily phase (medium chain triglycerides + CV), 2% w/w surfactants (Tween 80®/Span 80®), and 93% w/w water, and was produced by ultrasonication. Dynamic light scattering over 90 days was used to characterize CVNE. Cytotoxic activity and quantification of cytokines were evaluated in peripheral blood mononuclear cell (PBMC) culture supernatants. CVNE achieved a drug loading of 4.29 mg/mL, droplet size of 165.70 ± 0.46 nm, polydispersity index of 0.14 ± 0.03, zeta potential of −10.25 ± 0.52 mV, and good stability for 90 days. CVNE showed no cytotoxicity at concentrations up to 200 µM in PBMCs. CV diminished the production of IL-2 in the PBMC supernatant. However, CVNE reduced the levels of the pro-inflammatory cytokines IL-2, IL-17, and IFN-γ at 50 µM. In conclusion, a stable CVNE was produced, which improved the CV immunomodulatory activity in PBMCs.